Attitudes of Young Adults Towards Cleaning Agents - Aulanko, Marja (Nurture, 2007)
The variety of cleaning agents in the market is huge and a consumer may have difficulties in making a choice. The aim of this research was to find out what young adults think about cleaning agents. The material was collected from Finnish and British university students who wrote down their thoughts about cleaning agents. Four themes were emphasized in the writings: marketing, technical factors, lifestyle and knowledge. The young adults’ attitudes were largely unanimous, whether or not the respondents had studied cleaning issues. However, the British respondents emphasized safety issues, while the Finnish students emphasized environmental themes. The knowledge which the students desired concerned the basics of cleaning regardless of the respondents’ background.